A simple way to synthesize 3D hierarchical HAp porous microspheres with sustained drug release. Issue 9 (November 2015) - Yang, Chen; Lin, Kaili; Chang, Jiang
Abstract: In this paper, a simple and environmentally friendly strategy was developed to synthesize the sphere-like hierarchical structures of HAp which was transformed by using flower-like CaHPO4 as a precursor in NaOH solution. Self-assembly flower-like CaHPO4 can be synthesized in mixed solvents of water and ethanol via microwave-assisted method. The effects of the reaction conditions on the morphology of the product were investigated and a possible formation mechanism was proposed. Furthermore, CaHPO4 microflowers can be transformed to HAp with sphere-like hierarchical structure with the assistance of microwave irradiation. These HAp porous microspheres exhibited high drug-loading capacity and sustained drug release properties due to their novel 3D hierarchical mesoporous structures and high specific surface area. Our study indicated that the fabricated hierarchical HAp porous microspheres might be a potential candidate as drug-delivery biomaterials for hard tissue repair.